2019
DOI: 10.1021/jacs.9b03978
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Decarboxylative Cyclization/Alkenylation Strategy for Total Syntheses of (+)-Longirabdiol, (−)-Longirabdolactone, and (−)-Effusin

Abstract: Structurally complex and bioactive ent-kaurane diterpenoids have well-characterized biological functions and have drawn widespread attention from chemists for many decades. However, construction of highly oxidized forms of such diterpenoids still presents considerable challenges to synthetic chemists. Herein, we report the first total syntheses of C19 oxygenated spiro-lactone ent-kauranoids, including longirabdiol, longirabdolactone, and effusin. A concise synthesis of the common intermediate used for all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 75 publications
0
11
0
1
Order By: Relevance
“…Here,wediscuss the first syntheses of these natural products by Li and co-workers,who made use of decarboxylative tactics for the formation of key C À C bonds. [58] Specifically,L ia nd co-workers envisioned that the bicyclo[3. Li and co-workers began their synthesis with ak nown five-step sequence,i nw hich commercially available ethyl 2cyclohexanonecarboxylate was converted enantioselectively into carboxylic acid 196;i na na dditional three steps, Nacyloxyphthalimide 197 was synthesized, which serves as ap recursor for the key tandem decarboxylative cyclization/ alkenylation sequence (Scheme 24 B).…”
Section: Reviewsmentioning
confidence: 99%
“…Here,wediscuss the first syntheses of these natural products by Li and co-workers,who made use of decarboxylative tactics for the formation of key C À C bonds. [58] Specifically,L ia nd co-workers envisioned that the bicyclo[3. Li and co-workers began their synthesis with ak nown five-step sequence,i nw hich commercially available ethyl 2cyclohexanonecarboxylate was converted enantioselectively into carboxylic acid 196;i na na dditional three steps, Nacyloxyphthalimide 197 was synthesized, which serves as ap recursor for the key tandem decarboxylative cyclization/ alkenylation sequence (Scheme 24 B).…”
Section: Reviewsmentioning
confidence: 99%
“…16 By contrast, copper salts were incompetent (entry 10). 17 Replacement of PBI with other pyridine-containing additives did not improve the results (entries 11-13). While other independent hydrogen sources such as H 2 , BH 3 , and H 2 O, were not suitable (entries 14-16 and Supporting Information, Table S2).…”
Section: Cluster Synlettmentioning
confidence: 99%
“…to make the key intermediate 42.1 using decarboxylative radical cross-coupling in a sequential radical cyclization/alkenylation cascade (Scheme 42). 33 After extensive exploration of catalysts, ligands, additives as well as reaction conditions, compound 42.1 was obtained in good yield through a sequential Cu-catalyzed decarboxylative cyclization/alkenylation. Encouraged by this success, Li and coworkers further explored the generality of the reaction by using a broad range of substrates and vinyl bromide part-ners (Scheme 42).…”
Section: Review Synthesismentioning
confidence: 99%
“…Encouraged by this success, Li and coworkers further explored the generality of the reaction by using a broad range of substrates and vinyl bromide part-ners (Scheme 42). 33 It was demonstrated that this robust process could deliver a variety of structurally diverse lactone ring systems, including those bearing quaternary centers. This synthetic strategy offered a streamlined approach to access sterically congested terpenoid systems, as exemplified by the synthesis of three natural products.…”
Section: Review Synthesismentioning
confidence: 99%